2019
DOI: 10.1016/j.chemosphere.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

First insight into human extrahepatic metabolism of flame retardants: Biotransformation of EH-TBB and Firemaster-550 components by human skin subcellular fractions

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…2019 ). Similarly, microsomal preparation of human skin demonstrated the ability of carboxylesterases to efficiently generate DPhP from TPhP ( Abdallah et al. 2019 ), indicating that the likelihood of TPhP reaching subcutaneous fat and blood through this route of exposure is very low.…”
Section: Introductionmentioning
confidence: 99%
“…2019 ). Similarly, microsomal preparation of human skin demonstrated the ability of carboxylesterases to efficiently generate DPhP from TPhP ( Abdallah et al. 2019 ), indicating that the likelihood of TPhP reaching subcutaneous fat and blood through this route of exposure is very low.…”
Section: Introductionmentioning
confidence: 99%
“…Although the default minimum peak intensity is 1,000,000 in Compound Discoverer, thresholds as low as 1000 have been used by others in metabolomics workflows successfully. 32,33 We chose a signal threshold of 2000 to maximize sensitivity so as to annotate as many suspect compounds as possible. This greatly increased the number of false positive peaks.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This was a difficult test for the software, given the low concentration of spikes, small injection volume, high resolution (reduced number of data points relative to lower resolution acquisition), and the low peak threshold. Although the default minimum peak intensity is 1,000,000 in Compound Discoverer, thresholds as low as 1000 have been used by others in metabolomics workflows successfully. , We chose a signal threshold of 2000 to maximize sensitivity so as to annotate as many suspect compounds as possible. This greatly increased the number of false positive peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies have shown that skin carboxylesterases participate in the metabolic transformation of pollutants. 41 Consequently, the metabolic processes of UVs in skin warrant further exploration.…”
Section: Dermal Uptake and Percutaneous Penetration Of Uvs In The Ski...mentioning
confidence: 99%